1990
DOI: 10.1007/bf00402616
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal cell surface-associated IgG in patients with primary Sj�gren's syndrome: in vitro evidence for immune complex binding

Abstract: In vivo deposits of IgG have previously been demonstrated in the epidermal intercellular area of clinically unaffected skin from 68% of patients with primary Sjögren's syndrome (primary SS). This study compared circulating IgG from patients with primary SS with that from secondary SS in their ability to bind normal human epidermal cells in vitro. We observed a granular pattern of IgG binding to the normal epidermal cell surfaces with 9 of 18 sera from patients with primary SS (50%), 3 of 19 sera from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The finding of autoantibodies other than anti‐RNP is consistent with the concept of epitope spreading in systemic autoimmunity 20 . Anti‐SSA/Ro and anti‐SSB/La antibodies may participate in the pathogenesis of photosensitive skin lesions, 21–23 and IgG anti‐SSA/Ro may be found at epidermal surfaces of primary Sjögren’s syndrome 24 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The finding of autoantibodies other than anti‐RNP is consistent with the concept of epitope spreading in systemic autoimmunity 20 . Anti‐SSA/Ro and anti‐SSB/La antibodies may participate in the pathogenesis of photosensitive skin lesions, 21–23 and IgG anti‐SSA/Ro may be found at epidermal surfaces of primary Sjögren’s syndrome 24 …”
Section: Discussionsupporting
confidence: 84%
“…20 Anti-SSA ⁄ Ro and anti-SSB ⁄ La antibodies may participate in the pathogenesis of photosensitive skin lesions, [21][22][23] and IgG anti-SSA ⁄ Ro may be found at epidermal surfaces of primary Sjögren's syndrome. 24 Velthuis et al 3 suggested in vivo ANA for the diagnosis of CTDs. They found a positive predictive value (PPV) of 88% whereas we found a PPV of around 75%.…”
Section: Discussionmentioning
confidence: 99%